Deskripsi Deskripsi Kemampuan Pengajuan Masalah Pada Materi SPLDV Ditinjau dari Gaya Belajar - Ayu Zulpiah Sulaiman; Sitti Rahmayani (Mandalika Mathematics and Educations Journal, 2023)
This type of qualitative research uses data collection techniques by means of a learning style test, a two-variable equation system problem submission test, and structured photography. The purpose of this study is to describe the formulation of math questions based on student’s learning styles. The results of this study are (i) visual students whose learning styles are better able to optimize their learning styles and better understand the information that has been given. This is evident from the questions posed by students which vary from structural syntactical relations using elements of tasks, relationships, and hypotheses. (ii) students with an auditory learning style are better able to optimize their learning style and can understand information better, this is reflected in various questions from students. Students can also ask different questions to generate new data in addition to existing data in the information. (iii) whereas the first student with a kinesthetic learning style can produce data by submitting a variety of problems/questions and is still able to understand the information well. In contrast to the second student whose learning style is kinesthetic, he cannot generate new data and cannot make assumptions when asking questions. (iv) Visual, auditory, and kinesthetic learning styles already understand the information well and can raise problems from the information that has been provided.